2015
DOI: 10.5502/ijw.v5i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Do sources of meaning differentially predict search for meaning, presence of meaning, and wellbeing?

Abstract: Meaning in life is vital for human wellbeing. Research has examined important sources of meaning: however, it has not yet investigated whether certain sources of meaning might be more predictive of overall meaning and wellbeing. A community sample of 247 individuals (30 -69 years) rated the degree of meaningfulness they experienced in certain domains and completed 11 wellbeing measures. Presence of meaning was positively predicted by family and interpersonal relations, and negatively by leisure activities; sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 46 publications
(44 reference statements)
3
26
0
2
Order By: Relevance
“…Other authors have also found that meaning in life scores are most strongly explained by the sources family and relationships (Grouden & Jose, 2015;Lambert et al, 2010;Lambert et al, 2013), while happiness has also been associated with more satisfying interpersonal relationships with family and friends (Diener & Seligman, 2002).…”
Section: Hedonic and Eudaimonic Well-beingmentioning
confidence: 94%
See 1 more Smart Citation
“…Other authors have also found that meaning in life scores are most strongly explained by the sources family and relationships (Grouden & Jose, 2015;Lambert et al, 2010;Lambert et al, 2013), while happiness has also been associated with more satisfying interpersonal relationships with family and friends (Diener & Seligman, 2002).…”
Section: Hedonic and Eudaimonic Well-beingmentioning
confidence: 94%
“…our first aim). However, sources might be very salient and therefore rated high on meaningfulness, but they may not contribute to the overall experience of meaning or other aspects of well-being (Grouden & Jose, 2015).…”
Section: Present Studymentioning
confidence: 99%
“…Asimismo, un bajo nivel de sentido de vida se relaciona con desesperanza, depresión, dependencia a sustancias, conductas autolesivas y suicidio, entre otras variables indicativas de disfuncionalidad psicológica (García-Alandete, Marco & Pérez, 2014; Kleiman & Beaver, 2013). De la misma manera, varios estudios informan de una relación negativa entre el sentido de vida y algunos trastornos mentales, y relaciones positivas entre el sentido de vida y la salud mental, el funcionamiento psicológico, el optimismo, la satisfacción vital, la aceptación de la enfermedad y el bienestar psicológico, tanto en preadolescentes y adolescentes (Brassai, Piko & Steger, 2011;Mulders, 2011;Rathi & Rastogi, 2007) como en adultos y personas mayores (Burrow, Sumner & Ong, 2014;Grouden & Jose, 2015;Krause & Hayward, 2014), profesores (Damásio, de Melo & da Silva, 2013), y pacientes con cáncer (Scrignaro et al, 2015), con dolor crónico (Dezutter, Luyckx & Wachholtz, 2015) y con cuidados de enfermería a domicilio (Gorill, 2013;Haugan & Mosknes, 2013).…”
Section: Introductionunclassified
“…For example, Marar (2003) contrasts freedom and justification (or meaningmaking) in his conceptualization of happiness. Meaning-making entails creating a sense of order and purpose in life through the pursuit of goals (Grouden & Jose, 2015). This way of viewing happiness as a balancing act between being able to do what one wants, but also being tied to meaningful people and activities, fits well with the notions that participants mention in their interviews.…”
Section: Figure 1 Happiness As Balancementioning
confidence: 77%